2010
DOI: 10.1017/s175173111000025x
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental hair follicle biology and fine fibre production in animals

Abstract: Hair 'fine' fibre is an important commercial product of farmed and certain wild animal species. The fibre is produced in follicles embedded in skin. These have properties in common with other tissues of the integument and have importance in determining yield and quality of fibre. Means of understanding and improving these characteristics are informed by knowledge of integumental and follicle biology. This paper reviews contemporary information that identifies the major fibre-producing species and their product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 101 publications
0
51
0
4
Order By: Relevance
“…The in vitro approach coupled with histological, immunohistochemical and in situ hybridisation methodology may be applied to facilitate investigation of intrinsic morphology and hair shaft elongation in such follicles. Of particular interest will be the patterns of keratinocyte proliferation and differentiation and role of candidate regulatory molecules (Galbraith, 2010) in producing the recognised hair growth phenotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro approach coupled with histological, immunohistochemical and in situ hybridisation methodology may be applied to facilitate investigation of intrinsic morphology and hair shaft elongation in such follicles. Of particular interest will be the patterns of keratinocyte proliferation and differentiation and role of candidate regulatory molecules (Galbraith, 2010) in producing the recognised hair growth phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The production of hair by follicles, which have epidermal and dermal constituents similar to other tissues of the integument, is a complex process. This has also been the subject of review in this symposium (Galbraith, 2010). It has parallels in fundamental regulatory mechanisms involving stem cells, and programmed cellular proliferation and differentiation, which occurs in typical development from conception to maturity of multicellular animals.…”
Section: Introductionmentioning
confidence: 96%
“…Except for the Extension locus located on chromosome 14 (Vage et al, 2003), other loci affecting colour patterns in sheep have yet to be identified. Further details on the biology of pigment production have been provided by Galbraith (2010). Several wool-keratin genes, which are often clustered in families, have been cloned in the last decades.…”
Section: Fibre Growth Patternmentioning
confidence: 99%
“…Hair fibre, synthesised from follicles located on the external integumental surface of the body (Galbraith, 2010a), is commonly regarded as a unique mammalian feature. It is assumed that mammalian hair evolved about 200 million years ago (Ruben, 1995;Meng and Wyss, 1997;Grigg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…goats, camels, South American camelids (SACs) and yak). The artificial selection resulted in marked changes with regard to follicle number, type, distribution, growth and even natural shedding (Allain and Renieri, 2010;Antonini, 2010;Galbraith, 2010a). The impact of these genetic manipulations on the adaptation and acclimatisation of the animals is not completely understood.…”
Section: Introductionmentioning
confidence: 99%